Immune Senescence, Immunosenescence and Aging - Lee, Kyoo-A; Flores, Rafael R.; Jang, In Hwa; Saathoff, Ashley; Robbins, Paul D. (Frontiers in Aging, 2022)
With aging, there is increased dysfunction of both innate and adaptive immune responses, which contributes to impaired immune responses to pathogens and greater mortality and morbidity. This age-related immune dysfunction is defined in general as immunosenescence and includes an increase in the number of memory T cells, loss of ability to respond to antigen and a lingering level of low-grade inflammation. However, certain features of immunosenescence are similar to cellular senescence, which is defined as the irreversible loss of proliferation in response to damage and stress. Importantly, senescence cells can develop an inflammatory senescence-associated secretory phenotype (SASP), that also drives non-autonomous cellular senescence and immune dysfunction. Interestingly, viral infection can increase the extent of immune senescence both directly and indirectly, leading to increased immune dysfunction and inflammation, especially in the elderly. This review focuses on age-related immune dysfunction, cellular senescence and the impaired immune response to pathogens.